2015
DOI: 10.1103/physrevstab.18.121002
|View full text |Cite
|
Sign up to set email alerts
|

First measurement and correction of nonlinear errors in the experimental insertions of the CERN Large Hadron Collider

Abstract: Nonlinear magnetic errors in low-β insertions can contribute significantly to detuning with amplitude, linear and nonlinear chromaticity, and lead to degradation of dynamic aperture and beam lifetime. As such, the correction of nonlinear errors in the experimental insertions of colliders can be of critical significance for successful operation. This is expected to be of particular relevance to the LHC's second run and its high luminosity upgrade, as well as to future colliders such as the Future Circular Colli… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
11
0

Year Published

2017
2017
2019
2019

Publication Types

Select...
5

Relationship

4
1

Authors

Journals

citations
Cited by 10 publications
(11 citation statements)
references
References 14 publications
0
11
0
Order By: Relevance
“…On their own these measurements cannot be used to determine corrections, as it is impossible to distinguish sources in IP1 and IP5. When comparing measurements of feed-down to tune as a function of crossing angle in IP1 however, it was found that the quadratic tune shift (ΔQ ∝ y 2 , dependent on IR-octupole errors) consistently showed a good agreement with predictions of the magnetic model [49]. An example is shown in Fig.…”
Section: A Normal Octupole Correction In the Atlas (Ir1) And Cms (Irmentioning
confidence: 82%
See 2 more Smart Citations
“…On their own these measurements cannot be used to determine corrections, as it is impossible to distinguish sources in IP1 and IP5. When comparing measurements of feed-down to tune as a function of crossing angle in IP1 however, it was found that the quadratic tune shift (ΔQ ∝ y 2 , dependent on IR-octupole errors) consistently showed a good agreement with predictions of the magnetic model [49]. An example is shown in Fig.…”
Section: A Normal Octupole Correction In the Atlas (Ir1) And Cms (Irmentioning
confidence: 82%
“…During LHC design it was assumed that nonlinear corrections in the IRs would be inferred directly from magnetic measurements performed during construction [47,48]. Comparison of beam-based measurements to models incorporating the magnetic measurements however, revealed significant discrepancies for several multipoles [49] which precluded straightforward application of the design strategy. Consequently greater emphasis has been placed on methods for beam-based study of the nonlinear errors in the experimental insertions at 6.5 TeV.…”
Section: Commissioning Of the Nonlinear Opticsmentioning
confidence: 99%
See 1 more Smart Citation
“…In the LHC, the combined effect of magnets' misalignments and measured triplets' field quality is such that it is not possible to provide reliable information to compute the correctors' optimal strength. Beam-based measurements are therefore mandatory, yet extremely difficult and time-consuming to perform [45]. Moreover, the physical observables probed in these experiments are only indirectly linked with DA, the ultimate figure-of-merit.…”
Section: B Comparison With Numerical Simulationsmentioning
confidence: 99%
“…ac dipoles were proposed in the LHC as a complementary tool to measure optics functions alongside the more conventional kickers (MKQ and MKA [8,9]). However over the years, the importance of the LHC ac dipoles [10,11] has grown and they have now become critical in correcting linear [12][13][14] and nonlinear [15][16][17] optics parameters. To such an extent that they are the single most important measurement method for the linear and nonlinear correction strategies in the LHC and for the High Luminosity LHC [18].…”
Section: Introductionmentioning
confidence: 99%